Refunding Noncallable Debt - Emery, Douglas R.; Lewellen, Wilbur G. (Journal of Financial and Quantitative Analysis, 1984)
Since Bowlin's [4] original article on the topic was published, a considerable literature on corporate bond refunding has developed. Most of that literature has concentrated on the question of how to measure the benefit to a company's shareholders of exercising the call provision associated with an outstanding debt issue (see [3], [12], [21], [26], [27], [29], and [31]). Among the related concerns have been the matters of whether there are valuation advantages to the deliberate issuance of discount—including “zero coupon”—bonds (see [9], [22], and [28]), and whether there can be profitable opportunities for refunding prior to maturity debt instruments that were issued at par but later trade at a discount (see [1], [2], [13], [15], [17], [18], and [23]).